Reasoning about Cardinal Directions between 3-Dimensional Extended Objects using Answer Set Programming. Issue 6 (November 2020) - Izmirlioglu, Yusuf; Erdem, Esra
Abstract: We propose a novel formal framework (called 3D-N CDC-ASP) to represent and reason about cardinal directions between extended objects in 3-dimensional (3D) space, using Answer Set Programming (ASP). 3D-N CDC-ASP extends Cardinal Directional Calculus (CDC) with a new type of default constraints, and N CDC-ASP to 3D. 3D-N CDC-ASP provides a flexible platform offering different types of reasoning: Nonmonotonic reasoning with defaults, checking consistency of a set of constraints on 3D cardinal directions between objects, explaining inconsistencies, and inferring missing CDC relations. We prove the soundness of 3D-N CDC-ASP, and illustrate its usefulness with applications.